THE EFFECTIVENESS OF MONOLOGUE INTEGRATED WITH WORD CARDS ON SPEAKING SKILL - Bagus Putra Krisdiana (Journal of English for Academic and Specific Purposes (JEASP), 2020)
Speaking skill can be practiced in various ways. To master it, the researcher researched by using one of them by integrating it with word cards. The researcher used monologue integrated with word cards to investigate whether the integration was effective or not in increasing speaking skill. This study was restricted to the eleventh graders of the public upper level of secondary school. By using a one-group pre-test and post-test design, treatments were given to the 30 learners for six meetings. To achieve the aim of the study, two tests were constructed, in which a pre-test was given before while a post-test was given after the treatments. After the treatments finished, the scores of both tests were compared. The data analysis showed that the mean score of the pre-test was 42.3 while the post-test was 71.4 where tvalue = 31.753 with significance = .000 or ttabel of df = 29 with significance level .05 = 2.045, which means tvalue ttabel or significance .05. The result showed that the learners gained a significantly higher score in the post-test if it was compared to the one in the pre-test. It means that monologue integrated with word cards was effective in increasing speaking skill.